The dynamics of inflation, exchange rates and the trade balance in a small economy: The case of Uganda. Issue 2 (22nd June 2018) - Yiheyis, Zelealem; Musila, Jacob
Abstract : Purpose: The purpose of this study is to examine the temporal relationships between inflation and exchange rate changes and their implications for the trade balance in Uganda, which saw persistent trade deficits, rising inflation and disinflation episodes, as well as significant exchange-rate realignments and other liberalization measures over the sample period considered. Design/methodology/approach: The short-run dynamics of the variables in question and the pattern of their long-run relationships are examined applying the bounds testing approach to cointegration on quarterly data. Findings: The estimates suggest that, in the long run, a real depreciation leads to an increase in inflation; and that both real depreciation and inflation exert no significant effect on the trade balance. The estimated short-run dynamics suggest a causal relationship between the trade balance and the real exchange rate and between the real exchange rate and inflation, which is also found responsive to developments in the foreign sector. Taken together, the short-run and long-run multipliers seem to provide a weak support for the J-curve effect, while no evidence is found for the presence of the S-curve effect. Originality/value: The study sheds light on the relationship among real exchange rate, inflation and the trade balance in the context of a small developing economy; it highlights that an improvement in the trade balance requires more than an appropriate exchange rate policy and underscores the importance of other policies in strengthening the external sector of the economy.